2013
DOI: 10.4236/ojas.2013.31001
|View full text |Cite
|
Sign up to set email alerts
|

Association between growth rates, age at first calving and subsequent fertility, milk production and survival in Holstein-Friesian heifers

Abstract: Age at first calving (AFC) affects the profitability of dairy enterprises. This study examined the relationships between AFC and subsequent fertility, milk production and survival up to third calving in UK Holstein-Friesian heifers; Study 1 comprised 134 consecutively born heifers from the same herd (AFC 764 ± 8 days) and Study 2 contained 445 heifers born on 17 farms (AFC 796 ± 6 days). Growth rates and fertility during rearing were monitored and animals were subse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0
4

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 66 publications
(85 citation statements)
references
References 38 publications
4
59
0
4
Order By: Relevance
“…A decrease in AFC from 27 to 24 months of age was associated with a 10% reduction in the odds of removal from the herd (Archer et al, 2013). This is echoed in a recent study, where heifers with an AFC of 23 to 25 months of age outperform later calving compatriots in terms of fertility, milk production and survival for first 5 years of life (Cooke et al, 2013). The main reason discussed for removal of first lactation heifers from a herd is due to poor fertility performance (Evans et al, 2006;Brickell and Wathes, 2011), with a high AFC being connected with worse fertility performance in the first lactation (Zavadilová and Zink, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…A decrease in AFC from 27 to 24 months of age was associated with a 10% reduction in the odds of removal from the herd (Archer et al, 2013). This is echoed in a recent study, where heifers with an AFC of 23 to 25 months of age outperform later calving compatriots in terms of fertility, milk production and survival for first 5 years of life (Cooke et al, 2013). The main reason discussed for removal of first lactation heifers from a herd is due to poor fertility performance (Evans et al, 2006;Brickell and Wathes, 2011), with a high AFC being connected with worse fertility performance in the first lactation (Zavadilová and Zink, 2013).…”
Section: Discussionmentioning
confidence: 84%
“…These differences may relate to differences in ages at which puberty is reached and/or nutritional management in different studies. A reduction in IGF-1 concentrations in beef heifers by immunisation against growth hormone releasing factor (GRF) reduced follicular growth and delayed puberty whereas treatment with bovine somatotrophin (bST) from 7 months of age increased IGF-1 levels and was associated with earlier puberty (Cooke et al, 2013). Interestingly the bST treatment did not alter growth rate but both backfat thickness and leptin concentrations were reduced in the treated animals.…”
Section: Timing Of Pubertymentioning
confidence: 97%
“…On the other hand, Simerl et al (1991) and Bach (2011) both reported that the AFC could be reduced to 22 months without an increased frequency of problems at parturition. At the other extreme, overconditioned animals are also at greater risk of calving problems and this is more likely to occur in animals with delayed first breeding or poor initial fertility which therefore have an increased AFC (Cooke et al, 2013).…”
Section: Influence Of Heifer Rearing System On Subsequent Performancementioning
confidence: 99%
See 1 more Smart Citation
“…Management decisions on planes of nutrition, housing, disease control and breeding all influence growth and development [3] [4]. This, in turn, will affect the age at conception and the age at first calving (AFC), which can have long term economic consequences [5].…”
Section: Introductionmentioning
confidence: 99%